Development of Polyvinylidene Fluoride - Polydimethylsiloxane (Pvdf-Pdms) Thin Film Composite (Tfc) Membrane For Co2/ N2 Gas Separation - Abdul Karim, Shaikh Abdul Nasir (2013)
The objectives of this research is to develop of Polyvinylidenefluoride (PVDF) – Polydimethylsiloxane (PDMS) Thin Film Composite (TFC) and study the membrane performance for gas separation of CO2/N2. The support PVDF membranes were prepared by dry wet phase inversion with 15 %w/v of PVDF and 82%w/v of N-methyl-2-pyrrolidone (NMP) as solvent and 3%w/v of water as non-solvent. Polydimethylsiloxane (PDMS) was coated on the support membrane to produce a composite membrane using a dip coating method using 10, 15, 20 ratio of PDMS/n-hexane. Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR) spectroscopy, to determine chemical properties and physical of membrane. The selectivity of CO2/N2 gas was determined by gas permeation test. From the results, the high selectivity of the membrane behavior selected as the new membranes for gas separation membranes future. After tested by gas permeation test, the result of development PVDF-PDMS-TFC membrane gave excellent performance in separating CO2/N2 with higher selectivity and permeability.